Lactobacillus brevis FROM GAMITANA (Colossoma macropomum) SHOWS PROBIOTIC POTENTIAL WITH ANTAGONISTIC ACTIVITY AGAINST Lactococcus garvieae PATHOGEN - TOLEDO VALDIVIEZO, Odalis Epifanía (2025)
Autochthonous probiotics derived from the host’s native microbiota can enhance gastrointestinal colonization, feed efficiency, disease resistance, and stress tolerance in aquaculture species. This study evaluated bacteria isolated from the intestine and gills of gamitana (Colossoma macropomum) based on key probiotic selection criteria, including tolerance to acidic conditions and bile salts, antagonistic activity against pathogens, antibiotic susceptibility, biofilm formation, and enzymatic activity. A total of 69 bacterial isolates were obtained using Man, Rogosa, and Sharpe (MRS) broth and Trypticase Soy Broth (TSB). Five isolates (7.2%) met all selection criteria and were molecularly identified as Lactobacillus brevis (IPIFAB2, IPIFAC1, BRALA1) and Lactococcus garvieae (G25, G23). L. brevis isolates showed moderate acid tolerance, with survival rates between 31 ± 2.04% and 36.4 ± 0.17% at pH 4. All selected strains tolerated bile salts; however, L. brevis maintained high viability (≥78% at 0.8%), while L. garvieae exhibited marked reductions at higher concentrations. Antagonistic activity was significantly greater in L. brevis, producing inhibition halos of 2.3 ± 0.1 to 3.9 ± 0.1 mm, compared with 1.2 ± 0.21 to 1.9 ± 0.12 mm for L. garvieae. Proteolytic activity was observed in three L. brevis strains, and six isolates demonstrated biofilm-forming capacity. All selected strains were susceptible to the antibiotics tested. Among them, L. brevis IPIFAB2 exhibited the strongest probiotic profile. Overall, L. brevis strains show considerable potential as autochthonous probiotics for C. macropomum aquaculture, contributing to improved fish health, disease prevention, and sustainable production.